Use of E-Learning by University Students in Malaysian Higher Educational Institutions: A Case in Universiti Teknologi Malaysia - Al-Rahmi, Waleed Mugahed; Alias, Norma; Othman, Mohd Shahizan; Alzahrani, Ahmed Ibrahim; Alfarraj, Osama; Saged, Ali Ali Gobaili; Abdul Rahman, Nur Shamsiah (Institute of Electrical and Electronics Engineers, 2018)
This paper examines university students' intention to utilize e-learning. In this paper, we apply and use the theory of a technology acceptance model. We employ the structural equation modeling approach with a SmartPLS software to investigate students' adoption process. Findings indicate that the content of e-learning and self-efficacy has a positive impact and substantially associated with perceived usefulness and student satisfaction, which impact university students' intention to utilize e-learning. Although e-learning has gained acceptance in universities around the world, the study of the intention to use e-learning is still largely unexplored in Malaysia. The developed model is employed to explain the university student's intention to utilize e-learning. The study concludes that university students in Malaysia have positive perceptions toward e-learning and intend to practice it for educational purposes.